CONSUMER PROTECTION AND PUBLIC HEALTH - Militaru, Ioana Nely (International Journal of Legal and Social Order, 2024)
One of the objectives of the European Union is to ensure a high level of protection for its citizens, an objective that cannot be achieved without guaranteeing the protection of the health, safety and economic interests of consumers. In the context of these concerns, the European legislator has integrated consumer protection into all relevant policy areas of European Union legislation. The central aim of this policy is the protection of citizens' health, although the main responsibility in this direction rests with the Member States. Looking beyond the borders of the member states and even of the European Union, the Covid-19 pandemic has proven that health is a priority and goes beyond the area of interest, which is limited to the borders of a state or a union of states, but has gained global relevance.